Effect of high intensity conditioning on aggregate size of fine sphalerite - 孙伟 谢泽军 胡岳华 邓美姣 易峦 何国勇 (Transactions of Nonferrous Metals Society of China, 2008)
High intensity conditioning（HIC） was used as a model to study the fundamental of fine sulphide particle flotation. The effect of impeller design, mechanical energy input, and agitation speed on aggregate size of fine sphalerite was tested. The aggregate size of fine sphalerite was measured with the Malvern Hydro 2000 Mastersizer. The results show that the size of aggregates of sphalerite particles ground for 3 min can be enlarged significantly with the activator and collector addition in HIC using the high energy impeller. The improved particle aggregation by using the high energy impeller is not directly related to a higher energy input into the system. With the same energy input into HIC, the aggregate size obtained with the high energy impeller is much coarser than that obtained with the low energy impeller. With the new impeller in HIC, the sphalerite aggregate size decreases with increasing agitation speed from 700 to 2 500 r/min. However, the recovery does not decrease until the agitation speed reaches 2 500 r/min.